2021
DOI: 10.3390/jcm10163612
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Impact of PD-1 and PD-L1 Inhibitors on Advanced Esophageal or Gastric/Gastroesophageal Junction Cancer Treatment: A Systematic Review and Meta-Analysis

Abstract: Programmed death 1 (PD-1) and PD ligand 1 (PD-L1) inhibitors have demonstrated varying effectiveness in treating esophageal or gastric/gastroesophageal junction (G/GEJ) cancer. Hence, this systematic review and meta-analysis evaluated the efficacy and safety of anti-PD-1/PD-L1 treatment in patients with esophageal or G/GEJ cancer by analyzing the types of medications. Randomized controlled trials comparing anti-PD-1/PD-L1 to control therapy were identified by searching PubMed, EMBASE, and ClinicalTrials.gov. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…This present systematic review and meta-analysis was performed to investigate the clinical efficacy of PD-1/PD-L1 inhibitors on advanced gastroesophageal cancer as well as the relationship between clinicopathological features and the curative effects of PD-1/PD-L1 inhibitors. Consistent with the results of previous meta-analyses ( Chen et al, 2021 ; Formica et al, 2021 ; Oh et al, 2021 ), we found that PD-1/PD-L1 inhibitors (monotherapy or combined with chemotherapy) were associated with a prolongation of OS in patients with esophageal cancer, gastroesophageal junction cancer and gastric cancer, and it should be emphasized that no significant improvement in PFS was observed. Although both OS and PFS are regarded as important survival outcomes of response efficacy in anticancer treatment, the link between the two has yet to be fully proved.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This present systematic review and meta-analysis was performed to investigate the clinical efficacy of PD-1/PD-L1 inhibitors on advanced gastroesophageal cancer as well as the relationship between clinicopathological features and the curative effects of PD-1/PD-L1 inhibitors. Consistent with the results of previous meta-analyses ( Chen et al, 2021 ; Formica et al, 2021 ; Oh et al, 2021 ), we found that PD-1/PD-L1 inhibitors (monotherapy or combined with chemotherapy) were associated with a prolongation of OS in patients with esophageal cancer, gastroesophageal junction cancer and gastric cancer, and it should be emphasized that no significant improvement in PFS was observed. Although both OS and PFS are regarded as important survival outcomes of response efficacy in anticancer treatment, the link between the two has yet to be fully proved.…”
Section: Discussionsupporting
confidence: 91%
“…Previously, subgroup analyses of markers affecting the efficacy of PD-1/PD-L1 inhibitors in gastroesophageal cancer were performed through two meta-analyses ( Formica et al, 2021 ; Oh et al, 2021 ), but given the limited number of studies included, inconsistency of research design and significant heterogeneity among the included studies, the credibility of their results and conclusions seemed limited. Hence, based on the latest evidence from randomized controlled trials (RCTs), an updated meta-analysis will be executed to probe the clinical efficacy of PD-1/PD-L1 inhibitors in advanced gastroesophageal cancer and the association between patients' clinicopathological features (therapeutic schedules, sex, age, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…In summary, PD‐1/PD‐L1 blockade therapy in gastric cancer should be certified further 50 . In addition, it is imperative to explore whether there are more factors to comprehensively evaluate suitable patients and cancer types for effective PD‐1/PD‐L1 blockade therapy in gastric cancer 51‐53 .…”
Section: Current Status Of Pd‐1/pd‐l1 Blockade Therapy In Gastric Cancermentioning
confidence: 99%
“…In summary, PD-1/PD-L1 blockade therapy in gastric cancer should be certified further. 50 In addition, it is imperative to explore whether there are more factors to comprehensively evaluate suitable patients and cancer types for effective PD-1/PD-L1 blockade therapy in gastric cancer. [51][52][53] Only by determining the adaptability of PD-1/PD-L1 blockade therapy can the ICIs for gastric cancer could get a breakthrough.…”
Section: Current S Tatus Of Pd -1/pd -L1 B Lo Ck Ade Ther Apy In G a ...mentioning
confidence: 99%
“…Tumor cells can escape the killing of tumor cells by T cells through downregulating MHC and upregulating the expression of inhibitory receptors such as PD-L1, CTLA-4, LAG-3, TIM-3 and TIGIT ( 32 34 ), and blocking the binding of these inhibitory receptors to ligands can restore T-cell anti-tumor activity ( 35 ). PD-1/PD-L1 monoclonal antibodies (mAbs) demonstrate significant anti-tumor effect and prolong overall survival (OS) in various malignancies ( 36 38 ). PD-1 is an immunosuppressive receptor that is highly expressed on TILs ( 35 ), whereas PD-L1 as the main ligand of PD-1 is highly expressed on the surface of tumor cells ( 39 ).…”
Section: Pd-1/pd-l1mentioning
confidence: 99%